Transformation of chronic disease management: Before and after the COVID-19 outbreak - Yu, Steven; Wan, Rongjun; Bai, Lu; Zhao, Bingrong; Jiang, Qiaoling; Jiang, Juan; Li, Yuanyuan (Frontiers in Public Health, 2023)
Adults with chronic diseases often experience a decline in their quality of life along with frequent exacerbations. These diseases can cause anxiety and impose a significant economic burden. Self-management is a crucial aspect of treatment outside of the hospital and can improve quality of life and reduce the financial burden resulting from unexpected hospitalizations. With the COVID-19 pandemic, telehealth has become a vital tool for both medical professionals and patients; many in-person appointments have been canceled due to the pandemic, leading to increased reliance on online resources. This article aimed to discuss various methods of chronic disease management, both traditional self-management and modern telehealth strategies, comparing before and after the COVID-19 outbreak and highlighting challenges that have emerged.